Recommendations for standards of monitoring during anaesthesia and recovery 2015 : Association of Anaesthetists of Great Britain and Ireland. (19th November 2015) - Checketts, M. R.; Alladi, R.; Ferguson, K.; Gemmell, L.; Handy, J. M.; Klein, A. A.; Love, N. J.; Misra, U.; Morris, C.; Nathanson, M. H.; Rodney, G. E.; Verma, R.; et al.
Summary: This guideline updates and replaces the 4th edition of the AAGBI Standards of Monitoring published in 2007. The aim of this document is to provide guidance on the minimum standards for physiological monitoring of any patient undergoing anaesthesia or sedation under the care of an anaesthetist. The recommendations are primarily aimed at anaesthetists practising in the United Kingdom and Ireland. Minimum standards for monitoring patients during anaesthesia and in the recovery phase are included. There is also guidance on monitoring patients undergoing sedation and also during transfer of anaesthetised or sedated patients. There are new sections discussing the role of monitoring depth of anaesthesia, neuromuscular blockade and cardiac output. The indications for end‐tidal carbon dioxide monitoring have been updated.